From apathy to obsession: the reactions of A. K. Chesterton and the British far right to imperial decline. (19th October 2016) - Mulhall, Joe
ABSTRACT: Mulhall sets out to explain how, contrary to what one might expect, imperial decline was rarely a pressing issue for the British far right, usually falling below both the perceived threats of Communism and immigration on their list of priorities. By first explaining these unexpected findings and then placing them in an international comparative context, new evidence emerges that supports those imperial historians who subscribe to the 'minimal impact' orthodoxy regarding the effect of empire on the metropole. In addition, however, those aspects of the radical right that did concern themselves with imperial decline, namely A. K. Chesterton and the League of Empire Loyalists, are explored in depth, revealing a peculiarly British form of conspiratorial antisemitism that blamed imperial decline on secret Jewish power. This strand of conspiracy thinking, best articulated by Chesterton, is traced back to its origin so as to illuminate the continuity of ideas and ideologies between the interwar and post-war periods within the British far right. The result is an article that contributes to several existing historiographical debates and provides an exploration of a less well-known aspect of the work of A. K. Chesterton and conspiratorial antisemitism more generally.